2000
DOI: 10.1080/07055900.2000.9649661
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric teleconnection patterns and severity of winters in the Laurentian Great Lakes basin

Abstract: We analyzed the relationship between an index of Great Lakes winter severity (winters 1950-1998) and atmospheric circulation characteristics. Classification and Regression Tree analysis methods allowed us to develop a simple characterization of warm, normal and cold winters in terms of teleconnection indices and their combinations. Results are presented in the form of decision trees. The single most important classifier for warm winters was the Polar/Eurasian index (POL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Resale or republication not permitted without written consent of the publisher events in the equatorial Pacific (Assel 1998, Assel & Rodionov 1998, Rodionov & Assel 2000. For example, Assel (1998) has demonstrated that the mean value of the WSI was 1.2°C higher (statistically significant at the 5% level) for the 6 strongest El Niño winters between 1950 and 1994 than its mean value for the other winters in that base period.…”
Section: Abstract: Great Lakes · Pacific Decadal Oscillation · El Nimentioning
confidence: 99%
See 4 more Smart Citations
“…Resale or republication not permitted without written consent of the publisher events in the equatorial Pacific (Assel 1998, Assel & Rodionov 1998, Rodionov & Assel 2000. For example, Assel (1998) has demonstrated that the mean value of the WSI was 1.2°C higher (statistically significant at the 5% level) for the 6 strongest El Niño winters between 1950 and 1994 than its mean value for the other winters in that base period.…”
Section: Abstract: Great Lakes · Pacific Decadal Oscillation · El Nimentioning
confidence: 99%
“…Assel & Rodionov (1998) have found that 46% of the lowest quartile of the observed annual maximum ice covers for the period 1963−1990 occurred during the mature phase of El Niño. The 1983 and 1998 El Niño events both had far-below-average ice cover in the lakes (Assel et al 2000). Using the multivariate ENSO index (MEI) (Wolter & Timlin 1993), Rodionov & Assel (2000) have shown that of 10 winters with strong ENSO events (MEI > 0.8) during the 1950−1998 period, 7 winters in the Great Lakes were warm, 3 were normal, and none were cold.…”
Section: Abstract: Great Lakes · Pacific Decadal Oscillation · El Nimentioning
confidence: 99%
See 3 more Smart Citations